VASCULAR MECHANISMS OF TRITERPENOID SAPONINS ISOLATED FROM Passiflora quadrangularis L. - Guerrero Pabón, Mario Francisco; Bareño, Lesly L; Puebla, Pilar; San Feliciano, Arturo (Vitae, 2020)
Background: Passiflora quadrangularis L. has antihypertensive and anxiolytic properties observed in experimental models. Objectives: The aim of this work was to establish the vascular effects exerted by two known monodesmosidic triterpene saponins, 3-O-β-D-glucopyranosyloleanolic acid (Compound 1) (not previously described for this plant) and, 3-O-[β-D-glucopyranosyl-(1→2)-β-D-glucopyranosyl] oleanolic acid (Compound 2), isolated from the ethanolic extract of Passiflora quadrangularis L. leaves. Methods: The structural elucidation was achieved by Nuclear Magnetic Resonance (NMR) experiments and High-Resolution Mass Spectrometry (HRMS). Aortic rings from Wistar rats, previously stimulated with phenylephrine (PE, 1µM) and washed, were exposed to cumulatively concentrations of compound 1 and compound 2 (10 to 400 µM). Ethanolic extract from leaves of P. quadrangularis L. (10 to 320 µg/mL) and clonidine (1nM to 100µM) were also used for comparison. Concentration-response curves of compounds 1 and 2 were examined in presence and absence of: endothelium, the alpha-2 antagonist yohimbine (1 and 100 µM), the alpha non-selective antagonist phentolamine (1µM), the alpha-1 antagonist prazosin (1µM) and the calcium channel blocker verapamil (10 and 100 µM). In addition, a cumulative response curve of acetylcholine (ACh, 10nM to 10µM) and sodium nitroprusside (SNP, 1nM to 100µM) were assayed in rings precontracted with compounds 1 and 2 (400 µM). Results: Compounds 1 and 2 elicited a vasoconstriction response in intact aorta rings in a similar way (pEC50: 3.92±0.01 and 4.09±0.01, respectively), the effect that did not change in denuded rings (pEC50: 3.90±0.01 and 4.11±0.01). The potency order (pEC50) of compounds 1 and 2 decreased according to the following: verapamil (3.53±0.01 and 3.90±0.02; p<0.05) < yohimbine (3.65±0.01 and 3.94±0.02; p<0.05) < prazosin (3.86±0.01 and 4.30±0.02) < phentolamine (4.05±0.02 and 4.05±0.01). SNP but not ACh, was able to decrease the vasopressor effect of compounds 1 and 2 (pIC50: 8.61±0.01 and 8.24 ± 0.15, respectively). Conclusions: Compounds 1 and 2 are key metabolites responsible for the ex vivo vasoconstrictor response induced by P. quadrangularis L. Activation of voltage-dependent calcium channels and/or α2-adrenergic receptors stimulation could be mechanisms implicated.